Anxiety and depression among patients before and after Percutaneous Coronary Intervention (PCI) at National Heart Institute (NHI) - Ho, Siew Eng; Syed Zulkifli Syed Zakaria; Raja Lexshimi RG; Santhna Letchmi; Hamidah Hassan; Razali Omar; Teoh, Koi Hong; Hanida Mokhtar (Penerbit UKM, 2007)
Percutaneous coronary intervention (PCI) is an invasive diagnostic investigation that may result in high level of anxiety and “fear of the unknown” among cardiac patients. An increment in anxiety among PCI patients will augment the level of stress and this extreme stress level will then aggravate depression. The objective of this study was to determine the incidence of anxiety and depression before and after PCI. This was a cross-sectional descriptive study. The Hospital Anxiety and Depression Scale (HADS) was used. It measured two elements, namely, the anxiety and depression levels of patients before and after PCI. This study was conducted in the cardiology wards Anggerik and Dahlia, and Day Care of the National Heart Institute, from January to February 2006. A sample of 61 patients before and after PCI who fulfilled the inclusion criteria were recruited in this study. Of these, 40 and 38 patients before and after PCI respectively, had low anxiety levels; while, 47 and 46 patients before and after PCI respectively, had low depression levels. Anxiety and depression levels before and after PCI were not significantly correlated to socio demographic status. However, a significant correlation (p<0.05) was found between anxiety and depression levels before and after PCI. The low levels of anxiety and depression seen among patients before and after PCI at National Heart Institute could possibly due to the adequate facilities and health education program provided by the physician, nurses and cardiac technician